2010
DOI: 10.1007/s10961-009-9148-9
|View full text |Cite
|
Sign up to set email alerts
|

R&D productivity and the organization of cluster policy: an empirical evaluation of the Industrial Cluster Project in Japan

Abstract: Industrial clusters have attracted increasing attention as important locations of innovation. Therefore, several countries have started promotion policies for industrial clusters. However, there are few empirical studies on cluster policies. This paper examines the effects of the "Industrial Cluster Project" (ICP) in Japan on the R&D productivity of participants, using a unique dataset of 229 small firms, and discusses the conditions necessary for the effective organization of cluster policies. Different from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 37 publications
7
62
0
7
Order By: Relevance
“…These countries, which are all regarded as coordinated market economies [27], conduct national cluster policies with large subsidies (including biotechnology in their target technology fields), and specify that each cluster should have a local management organization implementing the cluster policy. As we later describe, the Japanese government initiated cluster policies in 2001 that were strongly influenced by European policies [18].…”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…These countries, which are all regarded as coordinated market economies [27], conduct national cluster policies with large subsidies (including biotechnology in their target technology fields), and specify that each cluster should have a local management organization implementing the cluster policy. As we later describe, the Japanese government initiated cluster policies in 2001 that were strongly influenced by European policies [18].…”
Section: Methodsmentioning
confidence: 91%
“…In Japan, MEXT implemented the Knowledge Cluster Initiative (KCI) and the City Area Program (CAP) in 2002, which were reorganized and integrated into the Regional Innovation Cluster Program in 2010, while METI (Ministry of Economy, Trade and Industry) carried out another cluster policy, Industrial Cluster Project ( [18,19]). In the MEXT programs, universities and public research institutes play a central role in the clusters as the cores of research collaboration with private firms.…”
Section: Cluster Policies In Japanmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies have examined the impact of such policies on innovation. Nishimura and Okamuro (2011a) have studied the effects of participation in the Japanese Industrial Cluster Project on patenting and university collaboration. They did not find a significant effect of cluster participation on a firm's R&D productivity, but rather showed that participating firms collaborating with partners outside the cluster were more productive in terms of patent output.…”
Section: Clusters and Innovation Policymentioning
confidence: 99%
“…At the same time, there was an even larger number of publications on the network structures in particular industries or regions (e.g., Duysters and Vanhaverbeke 1996;M'Chirgui 2007;Nishimura and Okamuro 2011). A commonality of most of these studies is that they attribute regional patterns and temporal changes in the network structure to differences across countries in terms of their social, political, or technological conditions and the development of these conditions over time.…”
Section: Literature Reviewmentioning
confidence: 99%